Gavin Jantjes: To Be Free! A retrospective 1970-2023 / (3ZGaf jGfJS Cf Jdhf MQkG(B! (3eYQV GSJYGOj 1970(B-(32023s - AlQasimi, Hoor; Hassan, Salah M. (Sharjah; Sharjah Art Foundation, 2023)
Texts: Carmen Hassan, Salah M. Hassan, Hoor AlQasimi. 18 November 2023- 10 March 2024 @ Al Mureijah Art Spaces
English; Arabic
Keywords: Exhibition booklet; N4390-5098 Visual Arts. Exhibitions